Resveratrol for preventing medication-related osteonecrosis of the jaws in rats - Vitale, Marcelo; Corrêa, Mônica Grazieli; Ervolino, Edilson [UNESP]; Cirano, Fabiano Ribeiro; Ribeiro, Fernanda Vieira; Monteiro, Mabelle Freitas; Casati, Marcio Zaffalon; Pimentel, Suzana Peres (Wiley, 2023)
This study evaluated the effect of resveratrol (RES) on the prevention of medication-related osteonecrosis of the jaws (MRONJ) in ovariectomized (OVX) rats treated with zoledronate (ZOL). Fifty rats were distributed in five groups: SHAM (n = 10): non-ovariectomy + placebo; OVX (n = 10):ovariectomy + placebo; OVX + RES (n = 10):ovariectomy + resveratrol; OVX + ZOL (n = 10):ovariectomy + placebo + zoledronate; and OVX + RES + ZOL (n = 10):ovariectomy + resveratrol + zoledronate. The mandibles left sides were analyzed with micro-CT, histomorphometry, and immunohistochemistry. On the right side, bone markers gene expression was analyzed by qPCR. ZOL increased the percentage of necrotic bone and reduced the neo-formed bone compared to groups not receiving ZOL (p < 0.05). RES impacted the tissue healing pattern in OVX + ZOL + RES, reduced inflammatory cell infiltrate, and improved bone formation in the extraction site. Osteoblasts, alkaline phosphatase (ALP)-, and osteocalcin (OCN)-immunoreactive cells were lower in OVX-ZOL than in SHAM, OVX, and OVX-RES. The OXV-ZOL-RES had fewer osteoblasts and ALP- and OCN-cells than the SHAM and OVX-RES. The tartrate-resistant acid phosphatase (TRAP)-positive cells were reduced in the presence of ZOL (p < 0.05), while the TRAP mRNA levels increased with ZOL treatment, with or without resveratrol, compared with the other groups (p < 0.05). RES alone increased superoxide dismutase levels compared to OVX + ZOL and OVX + ZOL + RES (p < 0.05). In conclusion, resveratrol reduced the tissue impairment severity induced by ZOL; however, it could not prevent the occurrence of MRONJ.
Keywords: bisphosphonates; osteonecrosis; osteoporosis; ovariectomy; resveratrol; zoledronic acid